2009
DOI: 10.1111/j.1548-2456.2009.00049.x
|View full text |Cite
|
Sign up to set email alerts
|

Professionalization and Probity in a Patrimonial State: Labor Inspectors in the Dominican Republic

Abstract: Are international labor rights campaigns making a difference in Latin America? This article reveals that Dominican policymakers and bureaucrats are responding to foreign pressure by redoubling their commitment to a distinctively Franco-Iberian model of labor law enforcement, in which skilled labor inspectors use their discretion to balance society's demand for protection with the economy's need for efficiency. In so doing, they provide an alternative to traditional collective bargaining practices-which at leas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 38 publications
0
57
0
2
Order By: Relevance
“…This is more specific than the Declaration's reference to "the elimination of discrimination in respect of employment and occupation." 6 Rosado Marzán (2010), Schrank (2009), and Velásquez Pinto (2011) also point out that FTAs had positive effects on labor enforcement in Chile, Dominican Republic and El Salvador respectively.…”
Section: From Side Agreement To a Labor Chaptermentioning
confidence: 99%
See 1 more Smart Citation
“…This is more specific than the Declaration's reference to "the elimination of discrimination in respect of employment and occupation." 6 Rosado Marzán (2010), Schrank (2009), and Velásquez Pinto (2011) also point out that FTAs had positive effects on labor enforcement in Chile, Dominican Republic and El Salvador respectively.…”
Section: From Side Agreement To a Labor Chaptermentioning
confidence: 99%
“…A number of country studies, some of which were mentioned above, provide qualitative evidence of the effects of US FTAs on enforcement of labor law in several of the signing Latin American countries (Rosado Marzán, 2010;Monroy Gallego, 2012;Schrank, 2009;Toyama Miyagusuku, 2011;Vega Ruiz, 2009;Velásquez Pinto, 2011;Weller, 2011). 9 They all suggest a positive effect though a number of different channels, including an increase in the inspection agency budget, hiring of additional labor inspectors, training of labor inspectors, providing new vehicles and computers, implementing a new case management system, and ending the political appointment process and reclassifying inspectors into the career civil service.…”
Section: Estimating the Effect Of Ftas On Enforcementmentioning
confidence: 99%
“…Inspectors also serve as gateways to other parts of the state apparatus, bringing cases in courts and referring employers to government services (such as worker training). Due to their key role in strengthening weak institutions, scholars have begun to examine inspectorates in industrializing countries that have high levels of non-compliance (Marshall 2007;Piore and Schrank 2008;Pires 2008;Schrank 2009;Ronconi 2010). These studies have demonstrated that enforcement, when it does occur, can have an impact on labor market outcomes.…”
Section: Occupational Safety and Health Administration Of The United mentioning
confidence: 99%
“…By contrast, cases of successful enforcement in the literature tend to emphasize a set of bureaucratic characteristics that provide the inspectorate with high degrees of internal coherence (c.f. Piore and Schrank 2008;Pires 2008;Schrank 2009). …”
Section: Occupational Safety and Health Administration Of The United mentioning
confidence: 99%
See 1 more Smart Citation